2005
DOI: 10.1021/ja055112a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Electron Transport by Elastic Bending of Short DNA Duplexes. Experimental Study and Quantitative Modeling of the Cyclic Voltammetric Behavior of 3‘-Ferrocenyl DNA End-Grafted on Gold

Abstract: The dynamics of electron transport within a molecular monolayer of 3'-ferrocenylated-(dT)(20) strands, 5'-thiol end-grafted onto gold electrode surfaces via a short C2-alkyl linker, is analyzed using cyclic voltammetry as the excitation/measurement technique. It is shown that the single-stranded DNA layer behaves as a diffusionless system, due to the high flexibility of the ss-DNA chain. Upon hybridization by the fully complementary (dA)(20) target, the DNA-modified gold electrode displays a highly unusual vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
209
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(225 citation statements)
references
References 54 publications
14
209
2
Order By: Relevance
“…Demaille, Anne and co-workers investigated the behaviour of Fc-carrying ssDNA and dsDNA layers. 181,182 In cyclic voltammetry, ssFc-DNA layers are described as diffusionless systems with high flexibility and rapid dynamics. After hybridisation, the voltammetric behaviour is explained by the so-called elastic bending diffusion model.…”
Section: Electron-transfer Within Metal-containing Pnamentioning
confidence: 99%
“…Demaille, Anne and co-workers investigated the behaviour of Fc-carrying ssDNA and dsDNA layers. 181,182 In cyclic voltammetry, ssFc-DNA layers are described as diffusionless systems with high flexibility and rapid dynamics. After hybridisation, the voltammetric behaviour is explained by the so-called elastic bending diffusion model.…”
Section: Electron-transfer Within Metal-containing Pnamentioning
confidence: 99%
“…Such a change causes increase of distance between redox active label covalently attached to the probe from the surface of electrode. In consequence, the increase of electrons transfer resistance was observed (Anne et al 2006;Aoki et al, 2010;Farjami et al, 2011;Lai et al, 2006;Lubin et.al, 2009;Pavlovic et al, 2008;Yang et al, 2010). Such a system is called "on-off" mode of the electrochemical signal.…”
Section: Introductionmentioning
confidence: 99%
“…50 This model is not in contradiction to the observation that single mismatches in the ds-DNA may affect the ET characteristics since the bending elasticity of ds-DNA should be highly sensitive to the base sequence, mismatch, or improper pairing. 50 The elastic bending diffusion model could help to understand why in this work ET was not observed when the Tarlov procedure was applied. In line with this model, the following explanation is suggested: after the formation of a dense and highly ordered monolayer, it should not be possible for the flavin redox centers to approach the electrode surface close enough for ET.…”
Section: Discussionmentioning
confidence: 91%
“…As a result of electrochemical studies on a ds-DNA monolayer of 20 base pairs equipped with a ferrocenyl head group, it has been suggested that ET occurs directly between the ferrocenyl head and the electrode without any contribution of the DNA base stack. 44,50 ET is only possible due to the elastic bending motion of DNA, and an elastic bending diffusion model has been developed. 50 This model is not in contradiction to the observation that single mismatches in the ds-DNA may affect the ET characteristics since the bending elasticity of ds-DNA should be highly sensitive to the base sequence, mismatch, or improper pairing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation